Characterization of cultured rat oligodendrocytes proliferating in a serum-free, chemically defined medium. - Saneto, R P (1985)
A serumless, chemically defined medium has been developed for the culture of oligodendrocytes isolated from primary neonatal rat cerebral cultures. Combined together, insulin, transferrin, and fibroblast growth factor synergistically induced an essentially homogenous population (95-98%) of cells expressing glycerol-3-phosphate dehydrogenase (EC 1.1.1.8) activity to undergo cell division. Proliferating cels were characterized by several criteria: (i) ultrastructural analysis by transmission electron microscopy identified the cell type as an oligodendrocyte; (ii) biochemical assays showed expression of three oligodendrocyte biochemical markers, induction of both glycerol phosphate dehydrogenase and lactate dehydrogenase (EC 1.1.1.27), and presence of 2',3'-cyclic nucleotide 3'-phosphodiesterase (EC 3.1.4.37); and (iii) immunocytochemical staining showed cultures to be 95-98% positive for glycerol phosphate dehydrogenase, 90% for myelin basic protein, 60-70% for galactocerebroside, and 70% for A2B5. Few cells (less than 5%) stained positive for glial fibrillary acidic protein, and none were detected positive for fibronectin.